Do Baseline Scores or Comorbidities Affect Patient-reported Outcome Measures Following First Metatarsophalangeal Joint Arthrodesis? - Vidhi Adukia; Ashish Mishra; Martin Hughes; Linzy Houchen-Wolloff; Maitravaarun Burgula; Jitendra Mangwani (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Arthrodesis is the gold standard treatment for patients with end-stage arthritis of the first metatarsophalangeal joint (MTPJ). The Manchester Oxford foot questionnaire (MOxFQ) and Euro quality of life (Qol) 5 dimension (EQ-5D) are patient-reported outcome measures (PROMs) commonly used following MTPJ arthrodesis. However, the impact of baseline scores and patient comorbidities on these PROMs is not well studied. Aim: The aim of this study is to identify the change in PROMs measured by MOxFQ and EQ-5D following the first MTPJ arthrodesis and to determine if the baseline scores and/or presence of comorbidities affected the change observed. Methods: Data was collected prospectively from patients who had undergone the first MTPJ arthrodesis for end-stage arthritis. The dataset included common comorbidities, baseline PROMs and PROMs following surgery. Results: A total of 90 patients were identified, of which 52 had complete PROMs data. The mean age was 56.9 ± 17.8 years, and male to female ratio was 1:4. Comorbidities included diabetes (2%), hypertension (21%), rheumatoid arthritis (RA) (43%), and current smokers (10%). The majority of cases were unilateral (94%), and 37% of patients had ipsilateral additional foot procedures carried out concomitantly. A significant change was seen in all domains of the MOxFQ as well as in the MOxFQ and EQ-5D total (p < 0.01). Baseline scores of both PROMs significantly correlated with the change seen in the scores (r = 0.5 and 0.6, respectively, p < 0.001). The presence of RA was found to significantly reduce the change in the EQ-5D total (p < 0.05). Conclusion: Following the first MTPJ arthrodesis, statistically significant changes were observed in EQ-5D and MOxFQ total and all the MOxFQ subdomains. Baseline scores in both PROMs correlated well with the change in scores following surgery, suggesting that we may be able to identify a baseline score that could predict outcomes. The presence of RA dampened the change seen in the EQ-5D total, which should form part of preoperative (pre-op) discussions with patients.